Myeloperoxidase-antineutrophil cytoplasmic antibody (ANCA)-associated systemic vasculitis developed from ANCA negative renal limited vasculitis: A case report. Issue 51 (December 2017) - Li, Xiao-li; Xu, Peng-cheng; Chen, Tong; Yan, Tie-kun; Jiang, Jian-qing; Jia, Jun-ya; Wei, Li; Shang, Wen-ya; Hu, Shui-yi
Abstract: Rationale: The relationship between antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) and ANCA-negative vasculitis has not been elucidated. Patient concerns: A 64-year-old female with edema and proteinuria was admitted. A kidney biopsy indicated focal proliferative nephritis with crescents in 25% of glomeruli. Serum ANCA was negative. Eighteen months later, systemic symptoms emerged and acute kidney injury occurred. Serum ANCA against myeloperoxidase (MPO) turned positive. Repeated kidney biopsy showed more severe lesion than last time. Immunoglobulin (Ig)G was purified from serum obtained before the first kidney biopsy. Weak ANCA which could not be detected in serum was found in IgG. Diagnoses: MPO-ANCA-associated AAV developed from ANCA-negative renal-limited AAV. Interventions: The patient was treated with glucocorticoid. Outcomes: The serum creatinine decreased to 2.17 mg/dL a week later. MPO-ANCA turned negative when re-examined 3 weeks later. No relapse has been observed during follow-up for 6 months. Lessons: This is the first reported case about the spontaneous transformation from ANCA-negative renal-limited AAV to ANCA-positive systemic vasculitis. There might be a slow process of epitope spreading in the pathogenesis of disease. Physicians should try their best to detect the ANCA in the diagnose and treatment of ANCA-negative AAV.